O e-Learning na educação corporativa Mackenzie: uma parceria em construção - Bressan, Ricardo (2011)
This interdisciplinary study is an exploratory qualitative research that investigates the contributions and difficulties that the deployment of e-learning provided in the educational system in the Mackenzie Presbyterian Institute. The methodology used was qualitative exploratory, for which at all times we equip of data through consultation and analysis of company documents, questionnaire to student employees, interviews with managers of the institution. The theoretical reference that guided the analysis is based on the assumptions of the Knowledge Society, Distance Education and Organizational Culture. The results indicate changes in the attitudes of managers and staff, improving the training of persons involved, a significant increase in scope and frequency of training and development program and serving as a stimulus to other areas in the implementation of new distance learning courses. It Could infer that despite these contributions, we are faced with a scenario in which the human and technological infrastructure needs to be expanded. The study found, finally, there is need for inclusion of an awareness program with the leadership positioning the value of e-learning mode, the mass training to employees in order to familiarize them with the virtual environment for teaching and learning - Moodle, and the formalization of policies that strengthen and encourage participation in online courses. These needs are decisive factors for the consolidation of e-learning in the Mackenzie Presbyterian Institute.